The COVID-19 Pandemic and the Incidence of the Non-COVID-19 Pneumonia in Adults - Huang, Chienhsiu (Frontiers in Medicine, 2021)
Introduction: The coronavirus disease 2019 (COVID-19) lockdown strategies were associated with a significant decrease in the common respiratory viral diseases and decreased the need for hospitalization among children in the COVID-19 outbreak. However, the trend of non-COVID-19 pneumonia in adult people remains uncertain. Our aim is to assess the impact of the COVID-19 pandemic on the incidence of the non-COVID-19 pneumonia in adult people and understand whether the substantial decrease in pneumonia cases is the same as the decline in the incidence of respiratory viral disease activity. Methods: We conducted a retrospective analysis of adult patients presenting with pneumonia from January 2019 to December 2020. Details on all the demographics of the patient of pneumonia, hospital course details, prior admission history within 3 months, respiratory culture, and antibiotics sensitivity test were also obtained. Results: The number of adult patients with community-acquired pneumonia in 2020 was lower than that in 2019, which decreased by 74 patients in 2020. The decreasing number of patients with community-acquired pneumonia between 2019 and 2020 was from −13.9% in January to March 2020 to −39.7% in October to December 2020. The decreasing number of patients with community-acquired pneumonia between 2019 and 2020 was from −14.8% in the youngest cohort to −28.7% in those aged ≥85 years. The number of reduced patients with community-acquired pneumonia is greater in late seasons and older age, respectively. The number of adult patients with hospital-acquired pneumonia in 2020 was lower than that in 2019, which decreased by 23 patients in 2020. The decreasing number of patients with hospital-acquired pneumonia between 2019 and 2020 was from −20.0% in January to March 2020 to −52.4% in October to December 2020. The decreasing number of patients with hospital-acquired pneumonia between 2019 and 2020 was from 0% in the youngest cohort to −45.6% in those aged ≥ 85 years. The number of reduced patients with hospital-acquired pneumonia is greater in late seasons and older age, respectively. Conclusion: Interventions applied to control the COVID-19 pandemic were effective not only in substantial changes in the seasonal influenza activity, but also in decreasing adult pneumonia cases.